PENGARUH CAPITAL INTENSITY DAN INVENTORY INTENSITY TERHADAP AGRESIVITAS PAJAK - Efrinal Efrinal; Afia Hilda Chandra (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of Capital Intensity and Inventory Intensity on Tax Aggressiveness. The sample used in this research is mining companies listed on the Indonesia Stock Exchange in 2015-2019 with 14 sample companies using purposive sampling method. The independent variables of this study are Capital Intensity and Inventory Intensity. The dependent variable of this study is Tax Aggressiveness as measured by the effective tax rate (ETR). The results show that Capital Intensity has a significant positive effect on Tax Aggressiveness. Meanwhile, Inventory Intensity has no significant effect on Tax Aggressiveness.